Increased mesolimbic cue-reactivity in carriers of the mu-opioid-receptor gene OPRM1 A118G polymorphism predicts drinking outcome: a functional imaging study in alcohol dependent subjects - Bach, Patrick; Vollstädt-Klein, Sabine; Sommer, Wolfgang H.; Spanagel, Rainer; Rietschel, Marcella; Kiefer, Falk (European neuropsychopharmacology, 2015)
The endogenous opioid system is involved in the pathophysiology of alcohol-use disorders. Genetic variants of the opioid system alter neural and behavioral responses to alcohol. In particular, a single nucleotide polymorphism rs1799971 (A118G) in the mu-opioid receptor gene (OPRM1) is suggested to modulate alcohol-related phenotypes and neural response in the mesocorticolimbic dopaminergic system. Little is known about the clinical implications of these changes. The current study investigated the relationship of genotype effects on subjective and neural responses to alcohol cues and relapse in a sample of abstinent alcohol-dependent patients. Functional magnetic resonance imaging (fMRI) was used to investigate alcohol cue-reactivity and drinking outcome of 81 abstinent alcohol-dependent patients. G-allele carriers displayed increased fMRI cue-reactivity in the left dorsal striatum and bilateral insulae. Neural responses to alcohol cues in these brain regions correlated positively with subjective craving for alcohol and positive expectations of alcohol׳s effects. Moreover, alcohol cue-reactivity in the left dorsal striatum predicted time to first severe relapse. Current results show that alcohol-dependent G-allele carriers׳ increased cue-reactivity is associated with an increased relapse risk. This suggests that genotype effects on cue-reactivity might link the OPRM1 A118G risk allele with an increased relapse risk that was reported in earlier studies. From a clinical perspective, risk-allele carriers might benefit from treatments, such as neuro-feedback or extinction-based therapy that are suggested to reduce mesolimbic reactivity.
Gesehen am 26.11.2018
Available online 18 April 2015